Feeling Threatened by the War in Ukraine: A Study in Italy on Identification, Entitativity and Attitudes Toward the EU - Francesco La Barbera; Carmela Altamura; Roberta Riverso (Europe's Journal of Psychology)
Russia’s invasion of Ukraine in February 2022 posed a practical and symbolic threat to EU citizens. Did this threat affect citizens’ identification with the EU? This was the main research question addressed in the current paper. In addition, we sought to evaluate whether the influence of perceived threat on the identification with the EU was mediated by perceived entitativity of the EU. Finally, we expected perceived threat to improve participants’ attitudes towards EU integration and enlargement, through the mediation of entitativity (Mediator 1) and identification with the EU (Mediator 2). We conducted a survey (N = 349, 186 females; Mage = 34.52) to assess this pattern of relations through structural equation models. Results show that perceived threat affects identification with the EU only indirectly, through the mediation of entitativity. In addition, perceived threat and entitativity have a significant indirect effect on attitude toward EU integration and attitude toward EU enlargement, yet they are directly associated only to the former. From a theoretical perspective, results are discussed in relation to previous research that shows the effect of perceived threat on identification, failing to consider the mediating role of entitativity. From a practical point of view, results may provide new insights on communication commonly used to reinforce the ingroup identity—mainly by threat-based strategies—through a re-consideration of the critical role of entitativity.